Profile of Crude Protein Tyrosine Kinase on Plasma Membrane of Merino Sheep Spermatozoa Using the Method of SDS-Page (Sodium Dodecyl Sulphate-Polyacrilamide Gel Electrophoresis) - Wardani, Vilda Carlenia; Madyawati, Sri Pantja; Hastutiek, Poedji (KnE Life Sciences, 2017)
The research aims to find out profile of crude protein tyrosine kinase on plasma membrane of Merino sheep spermatozoa. The research used fresh semen sample collected using artificial vagina technique, next it was centrifuged to separate spermatozoa from seminal plasma. Then, spermatozoa (pellet) was isolated. After obtaining spermatozoa isolate, analysis on protein tyrosine kinase using SDS-PAGE method was conducted. The method to analyze protein using SDS-PAGE to separate protein based on molecular weight. Analysis on molecular weight was conducted by comparing result of isolate tapes with protein marker tapes. Running on SDS-PAGE gel isolate protein plasma membrane of Merino sheep spermatozoa in the research resulted in 13 protein tapes with average molecular weights of 115.44 kDa; 95.78 kDa; 78.22 kDa; 69.02 kDa; 62.33 kDa; 53.72 kDa; 40.56 kDa; 30.74 kDa; 21.16 kDa; 13.67 kDa; 10.85 kDa; 9.49 and 8.07 kDa kDa. From this result, the second tape with the molecular weight of 95.78 kDa was believed to be protein tyrosine kinase tape however it needs to be confirmed further using Western Blot method. Keywords: tyrosine kinase, membrane of Merino sheep spermatozoa , SDS-PAGE